El efecto de entrenamiento de la velocidad diaria y su influencia en el rendimiento físico completo de los niños de la escuela de fútbol del gobierno autónomo descentralizado del cantón Paltas - Agila Arias, Jorge Fernando (2014)
This research aims to get to know about "The effect of daily training speed and its influence on the complete physical performance of children of school football Decentralized autonomous government of the canton Paltas" based on the problem of training Speed is not given properly and correctly, to do a general objective arose: Knowing the efficiency of speed training with ball on the soccer school of self-government decentralized the canton Avocados, and specific objectives: to identify the effect of training speed impinging directly or indirectly on children of College Football and analyze the efficiency of speed training with ball. The main methods in which this research was based were scientific method; Inductive Method - Deductive, it was on the hypotheses that will be tested during the development of research to arrive at the conclusions and generalizations; The Analytical Method - Synthetics, a description of the main aspects concerning took place and they have to do with the effect of speed and its impact on physical performance of children and the description method, details about training became speed, and the criteria that teachers and students will be made where data collection and research. The techniques applied were: Direct Observation Technique in the training process of the daily rate for the development of field research techniques, survey (60 students and 2 teachers) was used and observation sheet. The investigated population was established by 2 coaches and 60 athletes. Finally clear and relevant results are obtained among the most important we have 100% of athletes believe that if speed is essential in football, both for the player to field however, the speed goes hand in hand with the ability to advance, both are essential in the game and coaches claim that if you use activities or strategies to speed training in football because the strategies used may have expected results and improve errors.